Venous Stasis Leg Ulcers: A Review - David Gaus (Fundación Salud y Desarrollo Andino, Saludesa Ecuador, 2020)
Chronic venous stasis ulcers (CVSU) of the lower extremity affect up to 5% of the population over 65 years and 1.5% of the general population. CVSU is caused by chronic venous disease produced by venous hypertension. Venous hypertension results from valvular incompetence within the deep venous system, or by the obstruction of venous outflow. Both of these mechanisms produce poor venous return. Additionally, poor mobility and decreased calf muscle pump function are thought to be contributing factors. Life-long use of compressive therapy is indicated in patients with chronic venous disease in lower extremities. It reduces ambulatory venous pressure. These include bandaging systems, garments (stockings), or devices.